PENGARUH METODE INKUIRI BERBASIS BLENDED LEARNING DAN KREATIVITAS BELAJAR TERHADAP HASIL BELAJAR MAHASISWA PADA MATA KULIAH FISIKA UMUM I DI FMIPA UNIMED - Motlan .; Jurubahasa Sinuraya; Ratelit Tarigan (LPPM Universitas Negeri Medan, 2012)
The purpose of this study is to determine: (1) whether there was asignificant effect of blended learning method of inquiry-based learning outcomes, (2)whether there was an effect on the level of creativity learning learning outcomes,and (3) whether there was a significant interactive effect between methods of inquirybased blended learning and creativity of student learning outcomes.These includequasi-experimental study using a 2x2 factorial design. This study population isstudents of Department of Physics force in 2012. With scluster techniques make useof sampling, number of samples there `two classes, one class as the experimentalclass and the class as a control class. Each class totaled 45 people, so the totalnumber of samples is 90. The instrument used is twofold achievement test andquestionnaire creativity. To analyze the statistical data used two lanes anavaassisted SPPS version 7.0. Data were analyzed from a population of normal andhomogeneous bedistribusi.Based on the analysis and discussion, researchconclusions are: (1) there was a significant effect of blended learning method ofinquiry-based learning outcomes, (2) no effect of the level of creativity to learn theresults of studying physics, and (3) no significant interactive effect between methodsof inquiry-based blended learning and creativity student learning outcomes.